PENGEMBANGAN MEDIA PEMBELAJARAN FILM ANIMASI STOP MOTION PADA MATERI PANGKAT TIGA DAN AKAR PANGKAT TIGA UNTUK KELAS VI SD - Nurul Fadilah (Jurnal Ilmu Pendidikan dan Sosial, 2022)
Development of Learning Media for Stop Motion animated film on the cube of three and cube roots. The purpose of this study was to develop a stop motion animation film for mathematics learning media for sixth grade elementary school students on the power of three and cube roots and determine the feasibility of the developed media. The development model used in this research is ADDIE (Analyze, Design, Development, Implementation, Evaluation). The stages passed in this research and development include: (1) needs analysis, (2) design, (3) initial product development, (4) evaluation, (5) product revision. Evaluation of media and material products through the validation of media experts and material experts. The results of the assessment from media experts with an average score of 3.16 and material experts with an average score of 3.62. Overall the media can be categorized as good. Thus the mathematics learning media, stop motion animation films, material to the power of three and cube roots that have been developed are good or suitable to be used as learning media in schools.